THE INFLUENCE OF BURNOUT STUDY TOWARD STUDENTs ACHIEVEMENT - Syachrian Syahid, Muh. Alief; Sahade, Sahade; Rijal, Abdul; Anwar, Samsinar; Hasyim, Sitti Hajerah (Universitas Labuhanbatu, 2024)
This study aims toanalyze the effect of burnout study on the learning outcomes of students in the accounting expertise program at SMK Negeri 4 Makassar. The variables in this study are burnout studyas an independent variable and learning outcomes as a dependent variable. The population of this study is all students in the accounting expertise program at SMK Negeri 4 Makassar. The sampling technique uses theproportionate stratified random sampling technique, samples from the population are obtained from the entire population with a sample of 76 students. Data collection techniques used are questionnaires and documentation. Data analysis techniques used are percentage descriptive analysis, instrument test and hypothesis test. Based on the results of data analysis that has been carried out, the results of descriptive analysis of burnout study amounted to 44.78 percent which is classified as low and learning outcomes of 90.43 percent which are classified as very high. From the results of a simple linear regression analysis, a burnout study was obtained Ý = 84.602 + 0.094X which means that every addition of 1 burnout study value, the value of learning outcomes increased by 0.094. The results of the coefficient of determination analysis (r2) obtained the value (r2) = 0.024 which means that burnout study has a contribution to learning outcomes of 2.4 percent and the remaining 97.6 percent is influenced by other factors. While from the results of the t-test analysis obtained a significant value of 0.000<0.05 which means that burnout study has a significant positive effect on learning outcomes, thus the hypothesis is accepted. Keywords: Burnout Study, Learning Outcomes